1991
DOI: 10.7326/0003-4819-115-9-681
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Radiation Therapy Alone Compared with Combined Chemoradiotherapy for Locally Unresectable Non-Small Cell Lung Cancer

Abstract: Chemotherapy with MACC, in combination with thoracic radiotherapy, did not result in significant survival advantage compared with radiation alone (P greater than 0.2) in patients with medically inoperable or unresectable stage III non-small cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Combination chemoradiation therapy has improved survival in patients with stage III inoperable non-small cell lung cancer when compared with radiation treatment alone (1)(2)(3)(4)(5)(6)(7)(8)(9). Despite the promising improvement by combined modality therapy, investigations using various chemoradiotherapy combinations have yielded an average 5-year survival of less than 25%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination chemoradiation therapy has improved survival in patients with stage III inoperable non-small cell lung cancer when compared with radiation treatment alone (1)(2)(3)(4)(5)(6)(7)(8)(9). Despite the promising improvement by combined modality therapy, investigations using various chemoradiotherapy combinations have yielded an average 5-year survival of less than 25%.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promising improvement by combined modality therapy, investigations using various chemoradiotherapy combinations have yielded an average 5-year survival of less than 25%. While chemotherapy combinations have reached the plateau for non-small cell lung cancer (10), intrathoracic disease control is even more disappointing with an average low rate of control at 40-50% at best by radiographic criteria (1,4,6), and only 15%-17% control rate by tumor biopsy through post-treatment bronchoscopy (4). Because locoregional failure can serve as a continuous source of distant metastasis, improving chest disease control is critical in the management of locally advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of combined-modality therapy for inoperable stage III NSCLC is reported to vary and the reason for this is unclear, although differences between the eligibility criteria used in various studies may account for the different outcomes (Mattson et al, 1988;Morton et al, 1991;Sause et al, 1995). In the present study, the maximum tolerated dose of irinotecan was 60 mg m 72 .…”
Section: Clinicalmentioning
confidence: 75%
“…Some randomised trials showed improved survival with this approach (Dillman et al, 1990;LeChevalier et al, 1992), however others could not demonstrate the value of induction chemotherapy (Cullen et al, 1991;Mattson et al, 1991;Morton et al, 1991). A new approach would be simultaneous administration of chemotherapy and radiation therapy.…”
mentioning
confidence: 99%